Woman Economic Contribution, Livelihood Strategies, and Family Well-being of Farmer Families in Cimanuk Watershed - Fatimatul Muzakiyah; Hartoyo Hartoyo (Journal of Family Sciences, 2017)
The objective of this study were to analyze woman economic contribution, livelihood strategies, and well-being of farmer families in Cimanuk Watershed. This study used a cross-sectional study design. This research involved 65 samples farmer families. This study was conducted in Garut and Indramayu District. The results showed that most of woman economic contribution belong to low category. Livelihood diversification is a strategy that most farmer families do in the Cimanuk Watershed on the dry season, rainy season, disaster season, and highly economic pressure season. The family well-being of families belong to moderate category, and ecomonic well-being aspect occupied in lowly level than physic aspect, psychology aspect, and social aspect. The result showed that the well being of farmer families affected by woman economic contribution. The result also showed that livelihood strategies not affected to family well being. Many or less of livelihood strategies not affected to family well being.